ВОЛЕЙБОЛ СПЕЦИФИКАСИ ВА ВОСИТАЛАРИ АСОСИДА ПЕДАГОГИК МАҲОРАТНИ ШАКЛЛАНТИРИШ ИМКОНИЯТЛАРИ ҲАМДА ИСТИҚБОЛЛАРИ - Худайберганов, О.Э. (SCIENCE and SOCIETY, 2019)
The article deals with the education of professional enhancement of future teachers and specialists of physical education by means of volleyball, as well as about the influence of various sports on pedagogical skill.
Keywords: professional activity; training model; constructive activity; communication activity; active activity; physical education